Pathological description of a case of traumatology in porcupine (Coendou rufescens) - Duque-Arias, Santiago (2023)
The porcupine Coendou rufescens is a rodent with arboreal habits and climbing locomotion, but they can move easily on the ground occasionally, which has made them vulnerable to collisions due to being run over in natural areas immersed in urban areas with high traffic flow. This paper presents the case of an adult male porcupine being run over in the north of the Central Cordillera of Colombia, through the implementation of a radiographic and post mortem evaluation. The radiological study showed multiple fractures at the level of the skull, forelimbs, right rib cage, and vertebral bodies. The necropsy showed multiple injuries to the integumentary system, musculoskeletal system, and nervous system, including the presence of polytrauma to the head and neck, with loss of the upper part of the skull and heart rupture at the level of both atria. The most important findings included cardiac burst and skull fragmentation, making it difficult to establish the specific cause of death.